Genetic polymorphisms in the Interleukins IL1B, IL4, and IL6 are associated with concomitant periodontitis and type 2 diabetes mellitus in Brazilian patients - Cirelli, Thamiris [UNESP]; Nepomuceno, Rafael [UNESP]; Rios, Ana Cláudia S. [UNESP]; Orrico, Silvana R. P. [UNESP]; Cirelli, Joni A. [UNESP]; Theodoro, Letícia H. [UNESP]; Barros, Silvana P.; Scarel-Caminaga, Raquel M. [UNESP] (Wiley, 2020)
Objective: To assess whether single nucleotide polymorphisms (SNPs) in the IL10, IL1A, IL1B, IL4, TNFA, IL6, OPG, RANK, and RANKL genes, “classically” related with periodontitis, could be associated with susceptibility to T2DM, and also with both diseases concomitantly. Background: There are common pathogenic mechanisms in type 2 diabetes mellitus (T2DM) and periodontitis, but the knowledge of the genetic aspect of this is limited. In patients affected by concomitant T2DM and periodontitis, whose incidence is increasing, there is scarce information regarding the gene-phenotype association, including whether there are genes able to influence both diseases as comorbidities. Methods: Periodontal clinical parameters and biochemical profile (Insulin, Fasting Glycemia, HbA1c, Triglycerides, Total Cholesterol, HDL-cholesterol, and LDL-cholesterol) data were obtained from 894 individuals divided into following three groups: Healthy (H; n = 347), Periodontitis (P; n = 348), and Periodontitis + T2DM (P + T2DM; n = 199). DNA from oral epithelial cells was collected for genotyping. Associations between SNPs and pathologies were tested by multiple logistic regression models, adjusting for age, sex, and smoking habits. We also investigated whether there are sex or smoking effects of each SNP in these phenotypes. Results: The rs1143634-GA (IL1B) SNP showed significantly less likely to develop P + T2DM for all population and mainly for women (adjusted OR = 0.37, 95% CI = 0.16-0.88), while women carrying the rs224320 CT (IL4) were more susceptible to develop P + T2DM (adjusted OR = 1.81, 95% CI = 1.04-3.15). Men carrying the rs1800795-CC (IL6) genotype were less likely to develop T2DM (adjusted OR = 0.12, 95% CI = 0.02-0.70, P =.01). Conclusions: Some SNPs in the IL1B, IL4, and IL6 genes demonstrated sex-influenced association with concomitant periodontitis and T2DM, increasing the evidence of a common genetic component between these diseases and contributing with the understanding of their common pathogenic mechanisms.
Keywords: interleukin-1beta; interleukin-4; interleukin-6; periodontal diseases; single nucleotide polymorphism